2007
DOI: 10.1021/ie0704905
|View full text |Cite
|
Sign up to set email alerts
|

Wastewater Treatment Plant Synthesis and Design

Abstract: The most used process for biological nitrogen removal from municipal and industrial wastewaters is the activated sludge process. Because of the importance of this process, as well as the large number of existing facilities, a lot of research effort has been focused on optimizing the operation strategies or improving the individual plant design. However, the systematic optimization of the process structure (process synthesis) and operation conditions based on rigorous process models has not been presented in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 16 publications
1
33
0
1
Order By: Relevance
“…the influent characteristics, is required. Indeed, the computed optimal solution closely depends on the assumed wastewater flow rate and composition [28,34,38,39], as well as on the temporal variations of these characteristics [40], since they constitute the main source of disturbances of the ASP operation. While daily/weekly/seasonally variations of the wastewater characteristics due to human activity (the result of households' life-cycles and/or industrial activities) are quasi-periodic and can be reasonably estimated over the short and middle term, weather-related perturbations such as precipitation are unpredictable.…”
Section: Influent Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…the influent characteristics, is required. Indeed, the computed optimal solution closely depends on the assumed wastewater flow rate and composition [28,34,38,39], as well as on the temporal variations of these characteristics [40], since they constitute the main source of disturbances of the ASP operation. While daily/weekly/seasonally variations of the wastewater characteristics due to human activity (the result of households' life-cycles and/or industrial activities) are quasi-periodic and can be reasonably estimated over the short and middle term, weather-related perturbations such as precipitation are unpredictable.…”
Section: Influent Characteristicsmentioning
confidence: 99%
“…However, some studies [6,28,51] reported that, starting from different sets of initial conditions, their local-deterministic algorithm returned the same solution, whence the possibility that it might correspond to a global optimum. On the other hand, numerous studies adopting a multi-start procedure reported that the achieved results corresponded to a large number of local solutions [8,12,38,39,52,53].…”
Section: Effectiveness Of Various Optimization Techniquesmentioning
confidence: 99%
See 3 more Smart Citations